Synthetic RNA Silencing of Actinorhodin Biosynthesis in Streptomyces coelicolor A3(2). - Gabriel C Uguru; Madhav Mondhe; Shan Goh; Andrew Hesketh; Mervyn J Bibb; Liam Good; James E M Stach (PLoS ONE)
We demonstrate the first application of synthetic RNA gene silencers in Streptomyces coelicolor A3(2). Peptide nucleic acid and expressed antisense RNA silencers successfully inhibited actinorhodin production. Synthetic RNA silencing was target-specific and is a new tool for gene regulation and metabolic engineering studies in Streptomyces.